Cerebral vasculitis mimicking intracranial metastatic progression of lung cancer during PD-1 blockade. Issue 1 (20th June 2017) - Läubli, Heinz; Hench, Jürgen; Stanczak, Michal; Heijnen, Ingmar; Papachristofilou, Alexandros; Frank, Stephan; Zippelius, Alfred; Stenner-Liewen, Frank
Abstract : Background: Stimulation of the immune system by targeting the PD-1/PD-L1 pathway can result in activation of anti-tumor immunity. Besides its clinical benefit immune checkpoint therapy leads to significant immune-related adverse events (irAEs). Some rare irAEs are not well described yet but are critical in patient management. Case presentation: Here, we describe a case of autoimmune cerebral vasculitis/encephalitis after PD-1 inhibitor treatment for metastatic adenocarcinoma of the lung. Upon PD-1 blockade, the patient developed cerebral lesions, while having disease stabilization of extracranial metastases. Imaging suggested that the patient had new progressing brain metastases. Despite stereotactic irradiation the lesions progressed further. The largest lesion became symptomatic and had to be surgically resected. On examination, cerebral vasculitis was detected but not evidence of metastatic lung cancer. Analysis of the patient's serum revealed the presence of antinuclear antibodies that were already present before starting PD-1 blockade. In addition, we also found anti-vascular endothelial antibodies in the serum. Conclusion: This finding suggests that the patient had preformed autoantibodies and the checkpoint inhibitor induced a clinically relevant autoimmune disease. Taken together, encephalitic lesions in patients under PD-1/PD-L1 blockade can mimic metastatic brain lesions and this rare irAE has to be considered as a differential diagnosis in patients treated with immunotherapy.